Hot-melt injectable adhesive as well as preparation method and application thereof

By using ternary co-heating technology of α-lipoic acid, N-alkane lipoicamide, tris(2-carbonylethyl)phosphate hydrochloride or citric acid, co-heating products with small molecule eutectic phases are generated, which solves the problems of complex preparation of existing underwater adhesives, weak bonding strength and poor universality, and achieves long-lasting and stable bonding effect and good application performance underwater.

CN119823707AActive Publication Date: 2025-04-15SICHUAN UNIV

Patent Information

Application Number
CN202510034745.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

Existing bionic underwater adhesives have problems such as complex preparation, weak bonding strength and poor universality, which limits the development and application of underwater adhesives.

Method used

The ternary co-heating technology of α-lipoic acid, N-alkali lipoicamide, tris(2-carbonylethyl)phosphate hydrochloride or citric acid is used to generate co-heating products containing small molecule eutectic phases of α-lipoic acid and N-alkali lipoicamide in the phase, which has good injectable properties and long-lasting and stable adhesion underwater.

Benefits of technology

It achieves a lasting and stable bonding effect in the underwater environment, and has the advantages of green and environmental protection, simple preparation, good universality, strong adhesiveness and easy to use. It is suitable for daily life and industrial engineering fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823707A_ABST
    Figure CN119823707A_ABST
Patent Text Reader

Abstract

The invention discloses a hot-melt injectable adhesive as well as a preparation method and application thereof, and belongs to the technical field of adhesives. The hot-melt injectable adhesive provided by the invention contains a co-hot-melt product of alpha-lipoic acid, N-alkane lipoic amide and tris (2-carbonyl ethyl) phosphorus hydrochloride or citric acid, and specifically, the hot-melt adhesive is formed by cooling after the alpha-lipoic acid, the N-alkane lipoic amide and the tris (2-carbonyl ethyl) phosphorus hydrochloride or citric acid are subjected to mixing and hot melting. The hot-melt injectable adhesive provided by the invention adopts a temperature-responsive crystallization curing mode, the curing process does not involve substance exchange with a water phase, and the use of a solvent is omitted, so that the hot-melt injectable adhesive has the advantages of being green and environment-friendly, simple to prepare, good in universality, strong in adhesive force, convenient to use and easy to operate; the method is expected to show huge application potential in the fields of daily life and industrial engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of adhesives, and in particular relates to a hot-melt injectable adhesive and a preparation method and application thereof. Background Art

[0002] Underwater adhesives have broad application prospects in daily life, biomedicine and industrial engineering. However, achieving underwater bonding not only requires overcoming the influence of the hydration layer on the surface of the material on the interfacial adhesion, but also requires the adhesive itself to have suitable cohesive force or the ability to be cured underwater, making the development and design of underwater adhesives extremely challenging.

[0003] At present, many bionic underwater adhesives have been designed in the relevant technology inspired by marine organisms, such as the cross-linked copolymer of 2-(acryloyloxy)ethyltrimethylammonium chloride and 2-phenoxyethyl acrylate (ATAC-co-PEA) hydrogel designed by Gong Jianping et al.; the supramolecular cross-linked hydrogel of chitosan / tannic acid / silk fibroin designed by Yang Huanghao et al. These hydrogels generally achieve effective underwater adhesion through abundant weak interactions or covalent bonding.

[0004] However, existing bionic underwater adhesives generally have problems such as complex preparation, weak bonding strength and poor universality, which limit the development and application of underwater adhesives. Summary of the invention

[0005] The present application discloses a hot-melt injectable adhesive and a preparation method and application thereof, aiming to solve the technical problems of the existing bionic underwater adhesives, such as complex preparation, weak bonding strength and poor universality.

[0006] In order to achieve the above objectives, the technical solution adopted in this application is:

[0007] A first aspect of the present application provides a hot melt injectable adhesive comprising a co-hot melt product of the following components;

[0008] (i) α-lipoic acid;

[0009] (ii) N-Alkyl lipoamide;

[0010] (iii) tris(2-carbonylethyl)phosphine hydrochloride or citric acid.

[0011] In a preferred embodiment, the hot melt injectable adhesive comprises a co-melt product of the following components;

[0012] (i) 42-49 mol parts of α-lipoic acid;

[0013] (ii) 1 to 8 molar parts of N-alkyl lipoic acid amide;

[0014] (iii) 1 mol part of tris(2-carbonylethyl)phosphine hydrochloride or citric acid.

[0015] In a preferred embodiment, the N-alkyl lipoic acid amide has the following chemical structure:

[0016]

[0017] Wherein, R is a C6-C18 alkyl group.

[0018] The second aspect of the present application provides a method for preparing the hot melt injectable adhesive described in the present application, the steps of which include:

[0019] According to the raw material components of the hot-melt injectable adhesive described in the present application, α-lipoic acid, N-alkyl lipoic acid amide, and tris(2-carbonylethyl)phosphine hydrochloride or citric acid are mixed and hot-melted, and then cooled to obtain the hot-melt injectable adhesive.

[0020] In a preferred embodiment, the temperature of the mixed hot melt is 120-150°C.

[0021] The third aspect of the present application provides the use of the hot-melt injectable adhesive described in the present application for bonding a contact surface to be bonded.

[0022] In a preferred embodiment, when the bonding treatment is performed on the contact surface to be bonded, the hot-melt injectable adhesive is heated to 50-100° C. to melt, then injected onto the contact surface to be bonded and cooled.

[0023] In a preferred embodiment, the contact surface to be bonded is located in an aqueous system.

[0024] In a preferred embodiment, the aqueous system comprises a fresh water system, an acidic water system and / or a high salt water system.

[0025] A fourth aspect of the present application provides a glass bonding method, which comprises using the hot-melt injectable adhesive described in the present application to perform bonding treatment on the glass contact surface.

[0026] Compared with the prior art, the advantages or beneficial effects of the present application include at least:

[0027] The hot-melt injectable adhesive provided by the present application is effectively generated by ternary co-melting of α-lipoic acid, N-alkyl lipoamide and tri(2-carbonylethyl)phosphine hydrochloride or citric acid to form a co-melting product containing a small molecule eutectic phase of α-lipoic acid and N-alkyl lipoamide. On the one hand, when the temperature rises, the co-melting product can be given a high fluidity through the melting of the contained small molecule eutectic phase, so that it has good injectability; on the other hand, the fluid co-melting product can fully drain and wet the substrate underwater, and then form a wide range of weak interactions with the surfaces of different substrates through polar groups (-COOH, -NH-CO-), and can achieve a long-lasting and stable underwater curing and bonding effect through the recrystallization of the contained small molecule eutectic phase during the cooling process, giving it a long-lasting and stable bonding ability in the underwater environment. In addition, the injectable co-melt product prepared in the present application is a temperature-responsive crystallization solidification method. The entire solidification process does not involve material exchange with the water phase, and the solvent composition is omitted. It has the advantages of being green and environmentally friendly, simple to prepare, good universality, strong adhesion, and easy to use and operate. It is expected to show great application potential in daily life and industrial engineering. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0029] Figure 1 The temperature-increasing rheological curves of the hot-melt injectable adhesives PLAO2, PLAO4, PLAO8 and PLAO16 provided in this application;

[0030] Figure 2 Statistical graph of shear viscosity of 55°C melt of hot-melt injectable adhesives PLAO2, PLAO4, PLAO8 and PLAO16 provided in the present application;

[0031] Figure 3 Statistical graph of water contact angles of hot-melt injectable adhesives PLAO2, PLAO4, PLAO8 and PLAO16 provided in this application;

[0032] Figure 4 The lap shear strength test results of the hot-melt injectable adhesives PLAO2, PLAO4, PLAO8 and PLAO16 provided in this application, and the lap shear strength test results of PLAO8 adhered to glass underwater at different curing times;

[0033] Figure 5Actual picture of PLAO8 underwater adhesion weight provided for this application;

[0034] Figure 6 The lap shear strength test results of PLAO8 adhered to glass in acidic and high salt water environments provided in this application;

[0035] Figure 7 The shear viscosity curve of the hot-melt injectable adhesive PLAO8-CA at 55°C melt provided in this application;

[0036] Figure 8 The lap shear strength test results of the PLAO8-CA adhered glass provided in this application after 24 hours of curing;

[0037] Fig. 9 The experimental group and control group (TCEP+LA, LA+LA-C 18 、TCEP+LA-C 18 )'s shear viscosity variation curve of a 55°C melt;

[0038] Fig.10 The experimental group and control group (TCEP+LA, LA+LA-C 18 、TCEP+LA-C 18 ) Lap shear strength test results of the adhered glass after 24h curing. DETAILED DESCRIPTION

[0039] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments described in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0040] In the following description of this specification, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. Among them, A and B can be singular or plural; the symbol " / " means "or".

[0041] In the following description of this specification, the term "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of A, B or C", or "at least one of A, B and C" can mean any one of A, B, C, or A+B, or A+C, or B+C, or A+B+C, where A, B, C can be single or multiple, respectively.

[0042] In the following description of this specification, the order of serial numbers does not mean the order of execution. Some or all of the steps can be executed in parallel or one after the other. The execution order of each process should be determined by its function and internal logic, and does not constitute any limitation on the execution process of this embodiment.

[0043] In the following description of this specification, the numerical range should be understood to also specifically disclose each intermediate value between the upper and lower limits of the range. Any stated value or intermediate value in the stated range and any other stated value or each smaller range between the intermediate values ​​in the range are also included in this embodiment, and the upper and lower limits of the smaller range can be independently included or excluded in the range.

[0044] Unless otherwise specified, the technical / scientific terms used in this specification have the meanings commonly understood by those of ordinary skill in the art. Although this specification only describes preferred materials and methods, any similar or equivalent methods and materials may also be used in specific embodiments or test cases. All documents mentioned in this specification are incorporated by reference to disclose and describe methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0045] In a first aspect, an embodiment of the present application provides a hot melt injectable adhesive. The hot melt injectable adhesive of the present application comprises a co-thermal melt product of the following components;

[0046] (i) α-lipoic acid;

[0047] (ii) N-Alkyl lipoamide;

[0048] (iii) tris(2-carbonylethyl)phosphine hydrochloride or citric acid.

[0049] The co-melting product is a solidified product obtained by co-melting the α-lipoic acid, N-alkyl lipoamide and tri(2-carbonylethyl)phosphine hydrochloride or citric acid in the components and then cooling them.

[0050] In summary, the embodiment of the present application can generate a eutectic product containing a small molecule eutectic phase of α-lipoic acid and N-alkyl lipoic acid amide by setting a ternary eutectic melt of α-lipoic acid, N-alkyl lipoic acid amide and tri(2-carbonylethyl)phosphine hydrochloride or citric acid. On the one hand, when the temperature rises, the eutectic product can be given a high fluidity by melting the small molecule eutectic phase contained therein, so that it has good injectability; on the other hand, the high fluidity eutectic product can fully drain and wet the substrate underwater, and then form a wide range of weak interactions with the surfaces of different substrates through polar groups (-COOH, -NH-CO-), and can achieve underwater durable and stable solidification and bonding through recrystallization of the small molecule eutectic phase contained therein during the cooling process, giving it a durable and stable bonding ability in the underwater environment. In addition, given that the injectable co-melt product described in the present application is a temperature-responsive crystallization solidification method, the entire solidification process does not involve substance exchange with the water phase, and the solvent composition is omitted. It has the advantages of being green and environmentally friendly, simple to prepare, good universality, strong adhesion, and easy to use and operate, and is expected to show great application potential in daily life and industrial engineering.

[0051] The hot melt injectable adhesive according to the present disclosure preferably comprises a co-hot melt product of the following components;

[0052] (i) 42-49 mol parts of α-lipoic acid;

[0053] (ii) 1 to 8 molar parts of N-alkyl lipoic acid amide;

[0054] (iii) 1 mol part of tris(2-carbonylethyl)phosphine hydrochloride or citric acid.

[0055] It should be noted that the molar parts described in the present application refer to the direct or indirect proportioning of the α-lipoic acid, N-alkyl lipoamide and tris(2-carbonylethyl)phosphine hydrochloride or citric acid contained in the molar parts, which can be a direct combination of 42-49 molar parts of α-lipoic acid, 1-8 molar parts of N-alkyl lipoamide and tris(2-carbonylethyl)phosphine hydrochloride or 1 molar part of citric acid; it can also be an indirect combination of 4.2-4.9 molar parts of α-lipoic acid, 0.1-0.8 molar parts of N-alkyl lipoamide and tris(2-carbonylethyl)phosphine hydrochloride or 0.1 molar parts of citric acid; it can also be an indirect combination of 420-490 molar parts of α-lipoic acid, 10-80 molar parts of N-alkyl lipoamide and tris(2-carbonylethyl)phosphine hydrochloride or 10 molar parts of citric acid, etc.

[0056] The present application can effectively regulate the mechanical properties and adaptability of the prepared hot-melt injectable adhesive by controlling the molar content of α-lipoic acid, N-alkyl lipoamide and tri(2-carbonylethyl)phosphine hydrochloride or citric acid.

[0057] According to the hot melt injectable adhesive disclosed herein, the N-alkyl lipoic acid amide has the following chemical structure:

[0058]

[0059] In the formula, R is a C6-C18 alkyl group, specifically a straight-chain alkyl group or a branched-chain alkyl group containing 6 to 18 carbon atoms.

[0060] It should be noted that the present application can effectively regulate the hydrophobic properties of the prepared flowable co-melt product by controlling the number of carbon atoms of the substituent R shown in the above chemical structure, so that the co-melt product can fully drain water and wet the substrate underwater, thereby achieving a better long-lasting and stable bonding effect in an underwater environment. In a specific example, the N-alkane lipoamide includes but is not limited to N-hexyl lipoamide, N-dodecyl lipoamide, N-octadecyl lipoamide, etc.

[0061] It should be noted that the present application does not specifically limit the preparation method of the N-alkyl lipoamide, and it can be prepared by itself according to a known synthesis method. The present application provides a preparation method of N-alkyl lipoamide by taking the synthesis of N-octadecyl lipoamide as an example, which specifically comprises:

[0062] α-Lipoic acid (9.9 g, 48 mmol) and N-hydroxysuccinimide (5.5 g, 48 mmol) powders were added to 100 mL of dichloromethane, stirred and dissolved at 0 ° C, and then 72 mL of dichloromethane solution containing dicyclohexylcarbodiimide (12.4 g, 60 mmol) was added dropwise. The reaction mixture was reacted for 1 h at room temperature and then placed in a 4 ° C environment overnight. Subsequently, the reaction mixture was filtered and the solvent in the filtrate was evaporated under reduced pressure. After the filter residue was washed with ether twice, it was naturally dried at room temperature to obtain a light yellow powder, i.e., lipoic acid succinimide ester.

[0063] Thioctic acid succinimide ester (4.85g, 16mmol) and octadecylamine (7.0g, 23.4mmol) are dissolved in 200mL dichloromethane, react 36h under room temperature and nitrogen protection. After the reaction, organic phase is washed with 0.05M hydrochloric acid (500mL), saturated ammonium chloride solution (500mL) and saturated sodium chloride solution (500mL) successively. Organic phase after washing is dried over anhydrous magnesium sulfate, and solvent is evaporated under vacuum to obtain N-octadecyl thioctic acid amide.

[0064] Among them, by replacing the octadecylamine mentioned above with one of the C6-17 amines, the remaining N-alkyl lipoamides can be prepared respectively. For example, replacing octadecylamine with n-hexylamine can synthesize N-hexyl lipoamide; replacing octadecylamine with dodecylamine can synthesize N-dodecyl lipoamide, etc., which will not be described in detail in this article.

[0065] In a second aspect, the present application also provides a method for preparing the hot melt injectable adhesive described in the above application, preferably comprising:

[0066] According to the raw material components of the hot-melt injectable adhesive described in the present application, α-lipoic acid, N-alkyl lipoic acid amide, and tris(2-carbonylethyl)phosphine hydrochloride or citric acid are mixed and hot-melted, and then cooled to obtain the hot-melt injectable adhesive.

[0067] Among them, the preparation method of the embodiment of the present application can make the various components fully interact with each other and form a hydrophobic co-melt product containing a small molecule eutectic phase rich in α-lipoic acid and N-alkyl lipoamide, so that the co-melt product has good injectability and a long-lasting and stable adhesion effect in an underwater environment.

[0068] According to the preparation method disclosed herein, the temperature of the mixed hot melt is 120-150°C, specifically 120°C, 130°C, 140°C, 150°C or any one within the range. In particular, the embodiment of the present application controls the hot melt temperature so that α-lipoic acid, N-alkyl lipoamide and tris(2-carbonylethyl)phosphine hydrochloride or citric acid are fully melted and mixed, and physical combination and chemical reaction occur.

[0069] In the third aspect, the embodiment of the present application also provides an application of the hot melt injectable adhesive described in the above text application, specifically, the hot melt injectable adhesive described in the embodiment of the present application is used to perform bonding treatment on the contact surface to be bonded. Among them, in view of the fact that the hot melt injectable adhesive described in the present application has good injectability and a durable and stable underwater adhesion effect, after the hot melt injectable adhesive described in the present application is used to perform bonding treatment on the contact surface to be bonded, the bonded contact surfaces are firmly bonded, which can effectively reduce the shedding and separation between the contact surfaces.

[0070] According to the application of the present disclosure, it is found in specific application that the hot-melt injectable adhesive described in the present application can be melted and form a highly fluid co-melt product when heated to 50-100°C. Therefore, when the hot-melt injectable adhesive described in the present application is used for bonding the contact surface to be bonded, the hot-melt injectable adhesive can be heated to 50-100°C for hot melting, and then injected onto the contact surface to be bonded, and the contact surfaces to be bonded are brought into close contact and cooled to complete the bonding of the contact surfaces to be bonded.

[0071] According to the application of the present disclosure, since the hot-melt injectable adhesive described in the present application has a durable and stable adhesion effect underwater, the contact surface to be bonded described in the present application can be located in an aqueous system. The aqueous system specifically refers to a water-related environment, including but not limited to a freshwater system, an acidic water system and / or a high-salt water system.

[0072] In a fourth aspect, the embodiment of the present application further provides a glass bonding method, which includes using the hot-melt injectable adhesive described in the above text application to bond the glass contact surface. Among them, since the hot-melt injectable adhesive of the embodiment of the present application has good universality and a long-lasting and stable solidification bonding effect, after being used for bonding the glass contact surface, the bonded glass contact surface is firmly bonded and can maintain a long-lasting and stable bonding effect in an underwater environment.

[0073] The technical solution of the present application will be further described below in conjunction with specific embodiments.

[0074] Example 1

[0075] This embodiment provides a hot-melt injectable adhesive (PLAO2), the raw materials of which include:

[0076] 4.9 mmol (1.01 g) of α-lipoic acid powder;

[0077] 0.1 mmol (0.05 g) of N-octadecyl lipoamide powder;

[0078] 0.1 mmol (0.03 g) of tris(2-carbonylethyl)phosphine hydrochloride powder;

[0079] The above raw materials in molar proportions were put into a glass bottle, heated to 150° C. and stirred for 20 min, and then cooled and crystallized at room temperature to obtain a hot-melt injectable adhesive (PLAO2).

[0080] Example 2

[0081] This embodiment provides a hot-melt injectable adhesive (PLAO4), the raw materials of which include:

[0082] 4.8 mmol (0.99 g) of α-lipoic acid powder;

[0083] 0.2 mmol (0.09 g) of N-octadecyl lipoic acid amide powder;

[0084] 0.1 mmol (0.03 g) of tris(2-carbonylethyl)phosphine hydrochloride powder;

[0085] The above raw materials in molar proportions were put into a glass bottle, heated to 150° C. and stirred for 20 min, and then cooled and crystallized at room temperature to obtain a hot-melt injectable adhesive (PLAO4).

[0086] Example 3

[0087] This embodiment provides a hot melt injectable adhesive (PLAO8), the raw materials of which include:

[0088] 4.6 mmol (0.95 g) of α-lipoic acid powder;

[0089] 0.4 mmol (0.18 g) of N-octadecyl lipoic acid amide powder;

[0090] 0.1 mmol (0.03 g) of tris(2-carbonylethyl)phosphine hydrochloride powder;

[0091] The above raw materials in molar proportions were put into a glass bottle, heated to 150° C. and stirred for 20 min, and then cooled and crystallized at room temperature to obtain a hot-melt injectable adhesive (PLAO8).

[0092] Example 4

[0093] This embodiment provides a hot melt injectable adhesive (PLAO16), the raw materials of which include:

[0094] 4.2 mmol (0.87 g) of α-lipoic acid powder;

[0095] 0.8 mmol (0.37 g) of N-octadecyl lipoic acid amide powder;

[0096] 0.1 mmol (0.03 g) of tris(2-carbonylethyl)phosphine hydrochloride powder;

[0097] The above raw materials in molar proportions were put into a glass bottle, heated to 150° C. and stirred for 20 min, and then cooled and crystallized at room temperature to obtain a hot-melt injectable adhesive (PLAO16).

[0098] Example 5

[0099] This embodiment provides a hot melt injectable adhesive (PLAO8-CA), the raw materials of which include:

[0100] 4.6 mmol (0.95 g) of α-lipoic acid powder;

[0101] 0.4 mmol (0.18 g) of N-octadecyl lipoic acid amide powder;

[0102] 0.1 mmol (0.03 g) of citric acid powder;

[0103] The above raw materials in molar proportions were put into a glass bottle, heated to 150° C. and stirred for 20 minutes, and then cooled and crystallized at room temperature to obtain a hot-melt injectable adhesive (PLAO8-CA).

[0104] In order to verify the actual performance of the hot-melt injectable adhesive prepared in this application, the hot-melt injectable adhesives PLAO2, PLAO4, PLAO8, PLAO16 and PLAO8-CA prepared in Examples 1-5 were subjected to the following tests:

[0105] 1.1 Rheological characterization

[0106] The hot melt injectable adhesives PLAO2, PLAO4, PLAO8 and PLAO16 were made into sheets with a diameter of 8 mm and a thickness of 1 mm, and then tested in the temperature range of 0-80°C using a rotational rheometer equipped with a PP08 rotor and a temperature control platform. The results were as follows: Figure 1 As shown. Among them, Figure 1 The temperature-increasing rheological curves of hot-melt injectable adhesives PLAO2, PLAO4, PLAO8 and PLAO16.

[0107] according to Figure 1 It can be seen that the hot-melt injectable adhesives PLAO2, PLAO4, PLAO8 and PLAO16 prepared above all have high storage modulus (G') and loss modulus (G") in the low temperature range, and are significantly reduced during the heating process. Specifically, the modulus remains at a low level at temperatures of 55°C and above, indicating that the hot-melt injectable adhesives prepared in the examples of this application have good hot-melt behavior.

[0108] 1.2 Shear viscosity test

[0109] The hot-melt injectable adhesives PLAO2, PLAO4, PLAO8 and PLAO16 were heated to 55 °C and melted. The mixture was then stirred for 1 s using a rotational rheometer equipped with a PP08 rotor and a temperature control platform. -1 The shear viscosity test was carried out at a shear rate of Figure 2 As shown. Among them, Figure 2 This is a statistical chart of the shear viscosity of the 55°C melt of the hot-melt injectable adhesives PLAO2, PLAO4, PLAO8 and PLAO16.

[0110] according to Figure 2 It can be seen that the melt viscosity of the hot-melt injectable adhesives PLAO2, PLAO4, PLAO8 and PLAO16 prepared above gradually decreases with the increase of the added amount of N-octadecyl lipoamide. Specifically, the melt viscosity of PLAO8 and PLAO16 is lower than 100 Pa·s, which meets the injection requirements.

[0111] 1.3 Hydrophilicity and hydrophobicity test

[0112] After the hot-melt injectable adhesives PLAO2, PLAO4, PLAO8 and PLAO16 were made into flat sheets with a thickness of 1 mm, the water contact angle of each flat sheet was measured by the hanging drop method using an optical contact angle meter. The results are as follows: Figure 3 As shown. Among them, Figure 3 Statistical diagram of water contact angles of hot-melt injectable adhesives PLAO2, PLAO4, PLAO8 and PLAO16.

[0113] according to Figure 3 It can be seen that the water contact angles of the hot-melt injectable adhesives PLAO2, PLAO4, PLAO8 and PLAO16 prepared above are all approximately equal to or greater than 90°, and increase with the increase in the amount of N-octadecyl lipoic acid amide added, indicating that the hot-melt injectable adhesive prepared in the present application is hydrophobic, and the addition of N-octadecyl lipoic acid amide will significantly enhance the hydrophobicity of the prepared hot-melt injectable adhesive.

[0114] 1.4 Lap shear strength test

[0115] Soak a glass slide in water at room temperature to prepare it as a substrate;

[0116] After the hot-melt injectable adhesives PLAO2, PLAO4, PLAO8 and PLAO16 were loaded into a syringe and placed in a 55°C oven to melt, the melts of the hot-melt injectable adhesives PLAO2, PLAO4, PLAO8 and PLAO16 were respectively injected onto each glass substrate underwater to form an adhesion area, and then the adhesion area was covered with another glass sheet. After being immersed in water for different periods of time, PLAO-adhered glass samples were obtained. The PLAO-adhered glass samples were placed on a mechanical tester for tensile testing, and the results were as follows: Figure 4 As shown. Among them, Figure 4 A in the figure is the lap shear strength test result of PLAO adhered to glass after 24h curing; Figure 4 B in the figure is the lap shear strength test result of PLAO8 adhered to glass after being cured for different time periods.

[0117] according to Figure 4 As shown in A, the adhesion strength of PLAO to glass gradually increases with the addition of N-octadecyl lipoamide, but the adhesion effect is poor due to the sharp decrease in the number of polar groups providing adhesion in the PLAO16 structure, indicating that the addition of N-octadecyl lipoamide can improve the wettability and hydrophobicity of hot-melt injectable adhesives, thereby improving the underwater adhesion strength; according to Figure 4 As shown in B, the adhesion strength of PLAO8 to glass gradually increases with the extension of curing time and reaches stability at 7 days, indicating that the curing process of PLAO8 is controlled by time.

[0118] 1.5 Underwater rapid adhesion test

[0119] A 4 kg stainless steel weight was placed in water. The hot melt injectable adhesive PLAO8 was loaded into a syringe and placed in a 55 °C oven to melt it. The PLAO8 melt was injected onto the weight under water and then heated with a 2.5 cm 2 The stainless steel block is pressed onto the adhesion area, and the result is Figure 5 As shown. Among them, Figure 5 This is the actual picture of PLAO8 underwater adhesion weight.

[0120] according to Figure 5 It can be seen that after 5 minutes of curing, the hot-melt injectable adhesive PLAO8 prepared above firmly bonds the stainless steel block and the weight and can withstand the gravity of the 4kg weight, indicating that the hot-melt injectable adhesive PLAO8 has the performance of rapid underwater adhesion.

[0121] 1.6 Lap shear strength test of bonding in acidic and high salt water environment

[0122] The glass slide is immersed in an acidic and high-salt water environment at room temperature to prepare as a substrate;

[0123] The hot-melt injectable adhesive PLAO8 was loaded into a syringe and placed in a 55°C oven to melt it. Then, the PLAO8 melt was injected onto a glass substrate in an acidic and high-salt water environment to form an adhesion area. The adhesion area was then covered with another glass sheet and immersed in water for 7 days to obtain a PLAO8-adhered glass sample. The PLAO8-adhered glass sample was placed on a mechanical tester for tensile testing. The results were as follows: Figure 6 As shown. Among them, Figure 6 A in the figure is the lap shear strength test result of PLAO8 adhered to glass in an acidic water environment after 7 days of curing; Figure 6 Figure B is the lap shear strength test result of PLAO8 adhered to glass in a high salt water environment after 7 days of curing.

[0124] according to Figure 6 As shown in A, there is no significant difference in the glass adhesion strength of PLAO8 in acidic and neutral water environments with different pH values, indicating that the acidic environment has no significant effect on the adhesion performance of PLAO8. Figure 6 From B, we can see that there is no significant difference in the glass adhesion strength of PLAO8 in water environments with different salt concentrations, which indicates that different concentrations of salt ions have no significant effect on the adhesion performance of PLAO8.

[0125] 1.7 Shear viscosity test of PLAO8-CA

[0126] The hot-melt injectable adhesive PLAO8-CA was heated to 55 °C and melted. The rotational rheometer equipped with a PP08 rotor and a temperature control platform was used to -1The shear viscosity test was carried out at a shear rate of Figure 7 As shown. Among them, Figure 7 Shear viscosity curve of the hot melt injectable adhesive PLAO8-CA at 55°C.

[0127] according to Figure 7 It can be seen that the hot-melt injectable adhesive PLAO8-CA prepared above -1 The melt viscosity at a shear rate of less than 100 Pa·s meets the injection requirements.

[0128] 1.8PLAO8-CA lap shear strength test

[0129] Soak a glass slide in water at room temperature to prepare it as a substrate;

[0130] After the hot-melt injectable adhesive PLAO8-CA was loaded into a syringe and placed in a 55°C oven to melt, the hot-melt injectable adhesive PLAO8-CA melt was injected underwater onto each glass substrate to form an adhesion area, and then another glass sheet was used to cover the adhesion area. After soaking underwater for different periods of time, PLAO8-CA adhered glass samples were obtained. PLAO8-CA adhered glass samples were placed on a mechanical tester for tensile testing, and the results were as follows: Figure 8 As shown. Among them, Figure 8 The lap shear strength test results of PLAO8-CA adhered to glass after 24 hours of curing.

[0131] according to Figure 8 It can be seen that PLAO8-CA has good underwater adhesion effect similar to PLAO8, indicating that citric acid and tri(2-carbonylethyl)phosphine hydrochloride can be substitutes for each other.

[0132] In order to further illustrate the combined effect of the components contained in the hot melt injectable adhesive described in the present application, the performance of hot melts with different component combinations was tested using shear viscosity and lap shear strength as evaluation criteria. Specifically, the component ratio and preparation process of Example 3 were used as the experimental group (PLAO8), and comparative examples 1-3 were provided as control groups.

[0133] Comparative Example 1

[0134] This comparative example provides a binary co-thermal melt product of tri(2-carbonylethyl)phosphine hydrochloride and α-lipoic acid (TCEP+LA), i.e., N-octadecyl lipoamide (LA-C 18 ).

[0135] Comparative Example 2

[0136] This comparative example provides a binary co-melting product of α-lipoic acid and N-octadecyl lipoic acid amide (LA+LA-C18 ), that is, tris(2-carbonylethyl)phosphine hydrochloride (TCEP) is omitted from the composition.

[0137] Comparative Example 3

[0138] This comparative example provides a binary co-thermal product (TCEP+LA-C 18 ), i.e. α-lipoic acid (LA) is omitted from the composition.

[0139] 2.1 Shear viscosity test

[0140] The experimental group and the control group were heated to 55 °C, respectively, and a rotational rheometer equipped with a PP08 rotor and a temperature control platform was used to measure the flow rate at 0.1-100 s. -1 The shear viscosity test was carried out at a shear rate of Fig. 9 As shown. Among them, Fig. 9 The experimental group and the control group (TCEP+LA, LA+LA-C 18 、TCEP+LA-C 18 )'s shear viscosity change curve of the 55°C melt.

[0141] according to Fig. 9 It can be seen that the experimental group and the control group LA+LA-C 18 、TCEP+LA-C 18 At a shear rate greater than 1 s -1 The viscosity of the control group TCEP+LA was less than 100 Pa·s, which met the injection requirements; while the viscosity of the control group TCEP+LA was larger and difficult to inject.

[0142] 2.2 Lap shear strength test

[0143] Soak a glass slide in water at room temperature to prepare it as a substrate;

[0144] The experimental group and the control group were heated to a fully fluid state, and then injected into the glass substrate underwater to form an adhesion area. The adhesion area was then covered with another glass sheet. After being immersed in water for 24 hours, the adhered glass samples were placed on a mechanical tester for tensile testing. The results were Fig.10 As shown. Among them, Fig.10 The lap shear strength test results of the adhered glass in the experimental group and the control group after 24 hours of curing.

[0145] according to Fig.10 As shown in the figure, the underwater bonding strength of the experimental group to the glass is higher; the adhesion effect of the control group TCEP+LA is poor; the control group LA+LA-C 18 Compared with the control group TCEP+LA-C 18 No sticking effect.

[0146] In summary, the present application can generate a eutectic product containing a small molecule eutectic phase of α-lipoic acid and N-alkyl lipoic acid amide by setting a ternary eutectic melt of α-lipoic acid, N-alkyl lipoic acid amide and tri(2-carbonylethyl)phosphine hydrochloride. On the one hand, when the temperature rises, the eutectic product can be given a high fluidity by melting the contained small molecule eutectic phase, so that it has good injectability; on the other hand, the fluid eutectic product can fully drain and wet the substrate underwater, and then form a wide range of weak interactions with the surfaces of different substrates through polar groups (-COOH, -NH-CO-), and can achieve underwater durable and stable solidification and bonding through recrystallization of the contained small molecule eutectic phase during the cooling process, giving it a durable and stable bonding ability in the underwater environment. In addition, given that the injectable co-melt product described in the present application is a temperature-responsive crystallization solidification method, the entire solidification process does not involve substance exchange with the water phase, and the solvent composition is omitted. It has the advantages of being green and environmentally friendly, simple to prepare, good universality, strong adhesion, and easy to use and operate, and is expected to show great application potential in daily life and industrial engineering.

[0147] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0148] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.

Claims

1. A hot melt injectable adhesive, characterized in that: A co-melting product comprising the following components; (i) α-lipoic acid; (ii) N-Alkyl lipoamide; (iii) tris(2-carbonylethyl)phosphine hydrochloride or citric acid.

2. The hot melt injectable adhesive according to claim 1, characterized in that A co-melting product comprising the following components; (i) 42-49 mol parts of α-lipoic acid; (ii) 1 to 8 molar parts of N-alkyl lipoic acid amide; (iii) 1 mol part of tris(2-carbonylethyl)phosphine hydrochloride or citric acid.

3. The hot melt injectable adhesive according to claim 1 or 2, characterized in that: The N-alkane lipoic acid amide has the following chemical structure: Wherein, R is a C6-C18 alkyl group.

4. A method for preparing a hot melt injectable adhesive, characterized in that: The steps include: The raw material components of the hot-melt injectable adhesive according to any one of claims 1 to 3 are prepared by mixing and hot-melting α-lipoic acid, N-alkyl lipoic acid amide, and tris(2-carbonylethyl)phosphine hydrochloride or citric acid, and then cooling.

5. The preparation method according to claim 4, characterized in that: The temperature of the mixed hot melt is 120-150°C.

6. Use of the hot-melt injectable adhesive according to any one of claims 1 to 3 for bonding contact surfaces to be bonded.

7. The use according to claim 6, characterized in that: When the bonding treatment is performed on the contact surface to be bonded, the hot-melt injectable adhesive is heated to 50-100° C. to melt, then injected onto the contact surface to be bonded and cooled.

8. The use according to claim 7, characterized in that: The contact surfaces to be bonded are located in an aqueous system.

9. The use according to any one of claims 6 to 8, characterized in that: The aqueous system comprises a fresh water system, an acidic water system and / or a high salt water system.

10. A glass bonding method, characterized in that it comprises using the hot-melt injectable adhesive according to any one of claims 1 to 3 to perform bonding treatment on the glass contact surface.

Citation Information

Patent Citations

  • Preparation method of photo-crosslinking dynamic reversible supramolecular polymer adhesive based on lipoic acid small molecular compound

    CN113061263A

  • Preparation method of thioctic acid-based adhesive with high substrate adhesion

    CN118291084A

  • Lipoic acid-based deep eutectic supramolecular polymer adhesive as well as preparation method and application thereof

    CN118949109A

  • Preparation method of base tackifying polylipoic acid-based adhesive

    CN118995124A

  • use of gel-forming polymer, water, alcohol and seaweed extract to adjust the elasticity and adhesion of self-adhesive cosmetic polymer matrices

    DE10260872A1

Cited By

  • Preparation method and application of polythioctanamide compound

    CN122381340A